Outcome of an online laboratory to support a master program in remote engineering - Auer, Michael E.; Pop, Diana Vasilica; Zutin, Danilo Garbi [UNESP] (My University, 2012)
Active learning or working by means of online laboratories is especially valuable for distance working or education. The fact that users in the workplace can access remote laboratories without having to travel makes their flexibility one of the main characteristics of remote engineering. This flexibility is important for teleworking, education, and lifelong learning. As part of a European Union funded SOCRATES project, different universities have developed a Joint European Master Program in Remote Engineering (MARE) which includes a course of Rapid Prototyping of Digital Systems in its curriculum, designed by the Technical University Ilmenau, Germany. Implementing the laboratory part of this course as an Online Lab turned out to be a good solution to obtain better learning outcomes. The overall development and evaluation of the online solution was realized at Carinthia University of Applied Sciences, Villach Austria. © 2012 American Society for Engineering Education.